2018
DOI: 10.1161/circulationaha.118.034790
|View full text |Cite
|
Sign up to set email alerts
|

Study of Two Dose Regimens of Ticagrelor Compared With Clopidogrel in Patients Undergoing Percutaneous Coronary Intervention for Stable Coronary Artery Disease

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 35 publications
3
59
2
4
Order By: Relevance
“…In patients with CCS, the experimental strategy resulted in no significant difference in any clinical outcomes, but did lead to numerically higher rates of major bleeding in patients irrespective of their BMI group. Although Orme et al reported that lower platelet activity achieved with ticagrelor, compared with clopidogrel, also occurred in patients with CCS [41], our results might suggest that the anti-ischemic effect of potent P2Y 12 inhibitors may not be required in low ischemic-risk settings such as patients with CCS.…”
Section: Discussioncontrasting
confidence: 57%
“…In patients with CCS, the experimental strategy resulted in no significant difference in any clinical outcomes, but did lead to numerically higher rates of major bleeding in patients irrespective of their BMI group. Although Orme et al reported that lower platelet activity achieved with ticagrelor, compared with clopidogrel, also occurred in patients with CCS [41], our results might suggest that the anti-ischemic effect of potent P2Y 12 inhibitors may not be required in low ischemic-risk settings such as patients with CCS.…”
Section: Discussioncontrasting
confidence: 57%
“…A total of 80 potential eligible studies were then reviewed for full‐text evaluations, of which 39 articles were excluded because they did not meet the inclusion criteria (Table S1). Finally, 41 RCTs were included in the meta‐analysis with 23 trials comparing ticagrelor with clopidogrel and 18 trials comparing prasugrel with clopidogrel, in which bleeding data from ClinicalTrial.gov were used for the study of Ge 2010 . The selection steps and specific excluding reasons were shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Existing studies about the optimal DAPT regimen in stable CAD undergoing PCI are limited. In terms of pharmacodynamic effects, ticagrelor has shown greater platelet inhibition effect than clopidogrel in stable patients [29, 30]. In terms of clinical outcomes, GLOBAL LEADERS trail had evaluated the effects of ticagrelor and clopidogrel in stable CAD patients undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%